Յիշատակագրութեամբ գորգի եզակի օրինակը Ջէյմս Մարկ Քեշիշեանի անձնական հաւաքածուից - Պետրոսեան, Յասմիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Армянское культурное наследие осиротело после постепенного сокращения населения восточных регионов Армении в XIX—XX веках. Существует очень много культурных объектов с надписями, которые рассказывают многое об этих объектах. Таковым является ковер, хранящийся в частной коллекции Джеймса Марка Кешишяна. Он имеет уникальную надпись, опубликованную в книге М. Эланда: «Отрывки: Празднование обрядов перехода в армянских коврах с надписями» (Сан-Франциско, 2002 г.). В отчете обсуждается наш вариант прочтения надписи о дате, поводе создания ковра, имени ткачихи и ее происхождении. Ковер соткан в память о Святом Воскане. Изображенная на ковре структура имеет отношение к святилищам, названным именем Святого Воскана. В ходе исследования мы попытались отождествить структуру ковра с наиболее вероятным святилищем, названным именем Святого Воскана. Орнаменты на ковре объясняются в контексте восприятия души и подземного мира. The Armenian cultural heritage was orphaned after the gradual decrease in the population of the eastern regions of Armenia in the 19th—20th centuries. There are many cultural objects with inscriptions that tell a lot about the objects themselves. Such a rug is preserved in James Mark Keshishian’s private collection, which has a very unique inscription and has been published in M. Eiland’s book “Passages: Celebrating Rites of Passage in Inscribed Armenian Rugs”, San Francisco, 2002. The report discusses our version of reading the inscription about the date, the reason for the rug creation, the name and origin of the weaver. The rug was woven in memory of St. Voskan. The structure depicted on the rug is related to the sanctuaries named after St. Voskan. In the course of the study, we tried to identify the structure of the rug with the most probable sanctuary named after St. Voskan. The ornaments on the rug are explained in the context of perceiving the soul and the underworld.
Keywords: Հայ ժողովրդի մշակոյթ; Գորգագործութիւն